Penerapan Layanan E-health pada Puskesmas Kota Surabaya dalam Memberikan Pelayanan kepada Masyarakat: Literature Review - Ageng Rusbaya; Ernawaty Ernawaty (Faletehan Health Journal, 2024)
Globalization brought changes to traditional governance from paper-based administration to electronic governance services (e-government). The Surabaya City Government through the implementation of e-government formed e-health services to improve health services. The purpose of this study was to analyze the application of e-health services in health services at the Surabaya City Health Centers. The method of this research used a literature review study. The Publish on Perish application was used in Google Scholar searches with the keywords "implementation of E-health services", "E-health", "community health centers", and "implementation of E-health in the city of Surabaya" for the period 2016-2023 and on the https://app.covidence.org page to conduct screening so that 13 articles relevant to the topic were obtained. The implementation of e-health services had been implemented and some people and health workers felt the benefits, such as reducing queue volume, shortening patient waiting time, making it easier for patients to receive referral services, and being able to improve the performance of health center staff. However, there were still obstacles, including people who stuttered related to the use of technology, system errors, lights off, no helpdesk feature, patients did not cancel registration when they did not go to the health center, and patients who chose the wrong health centers. Based on this, the researcher concluded that the implementation of e-health had not been carried out properly and was not evenly distributed in all Surabaya City health centers.